Testimonies and experiences of patients awaiting transplant and transplanted patients in Italy: a survey aiming to understand their needs - Lia Bellis; Francesca Puoti; Alessia Troni; Valentina Caramia; Lucia Masiero; Silvia Pisanu; Salvatore Agrimano; Massimo Cardillo (Annali dell'Istituto Superiore di Sanità, 2023)
Introduction. Yersinia enterocolitica (Ye) species is divided into 6 biotypes (BT), 1A, 1B, 2, 3, 4, 5 classified based on biochemical reactions and about 70 serotypes, classified based on the structure of the lipopolysaccharide O-antigen. The BT1A is considered non-pathogenic, while the BT 1B-5 are considered pathogenic. Methods. Evaluate the distribution of eleven chromosomal and plasmid virulence genes, ail, ystA, ystB, myfA, hreP, fes, fepD, ymoA, sat, virF and yadA, in 87 Ye strains isolated from food, animals and humans, using two SYBR Green real-time PCR platforms. Results. The main results showed the presence of the ail and ystA genes in all the pathogenic bioserotypes analyzed. The ystB, on the other hand, was identified in all non-pathogenic  strains biotype 1A. The target fes, fepD, sat and hreP were found in both pathogenic biotypes and in BT1A strains. The myfA gene was found in all pathogenic biotype and in some Ye BT1A strains. The virF and yadA plasmid genes were mainly detected in bioserotype 4/O:3 and 2/O:9, while ymoA was identified in all strains. Conclusions. The two molecular platforms could be used to better define some specific molecular targets for the characterization and rapid detection of Ye in different sources which important implications for food safety and animal and human health.